(untitled) (Cadernos de Sociomuseologia, 2019)
The article analyses three museums – the Muzeum Romské Kultury in Czech Republic, the Muzej Romské Kulture in Serbia, and the Roma Ethnographic Museum in Poland – can be considered as elements of the Romani Nationalism. The main objective is to reflect on how these museums support a broad narrative about a common Indian origin of Gypsy/Romani populations. It is discussed how the aforementioned museums – by means of their exhibitions, websites, events or other any kind of official production – support sets of representations which allow a formation of an umbrella rhetoric about the groups known, taken and self-ascribed as Gypsies and/or Roma. The said rhetoric, then, is able to shelter all different groups within this population in a holistic manner, based on a narrative formed by essentializations, exoticizations and generalizations. The utmost layer of such practices it is an elaboration of a founding myth of their Indian Origins. This paper understands throughout that museums have a role in the process in which the concept of Roma is generalized in an attempt to rewrite and relabel Gypsy memory as a Roma history. Hence, considering the plurality that characterise the Gypsy/Romani people, it was necessary to articulate common aspects – whether truthful or not, is not the target of this article to discuss – which would legitimise this new identity, a Roma identity. This paper relies on the theories about memory, museology, sociomuseology, and the theory of representations. Key-words: Gypsy/Roma; Museums; Indian Origins; Nationalism.